Modelling Cyber‐Physical Systems Using Data‐driven Patterns. Issue 4 (12th January 2022) - Semeraro, Concetta; Lezoche, Mario; Panetto, Hervé; Dassisti, Michele
ABSTRACT: Modelling Cyber‐physical systems is quite complex and thus needs a big amount of data and modelling techniques representing the operational semantics of the modelled elements. Generally, the modelling action has a specific application type. For this reason, the paper proposes a series of modelling patterns aimed at automatically identifying invariant behaviors in the masses of data that can be modelled to emulate cyber‐physical systems and thus contribute to the digital transformation of industrial production companies.